(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses language vocabulary, lexical richness of a language, the transition of lexical units from one language into another, the phonetic phenomena that occur in the borrowings of Uzbek language, the combinatory and positional changes of sounds in speech and vocalisms in Persian-Tajik dialects